Knowledge, attitudes, and practices toward COVID-19 prevention in Yemen: a community-based cross-sectional study - Hassan, Ola El Hajj; Al-Aghbari, Ahmed Asa’ad; McGowan, Maureen; Dar Iang, Maureen; Basaleem, Huda Omer; Al-Sakkaf, Khaled Abdulla; Hyzam, Dalia; Jahn, Albrecht; Dureab, Fekri (Frontiers in Public Health, 2023)
BACKGROUND: Pandemics, especially in fragile war-torn countries like Yemen, challenge their already strained health systems. Community adherence to pandemic prevention measures is necessary to curb the severity of emerging pandemics – which is influenced by factors, such as people's knowledge and attitudes toward the pandemic. No studies in Aden have been published on the communities’ knowledge, attitudes, and practices (KAP) toward COVID-19 prevention to date. To understand adherence to pandemic prevention measures in contexts with fragile health systems, this study investigated KAP of Yemeni participants toward the COVID-19 pandemic. METHODS: We conducted face-to-face semi-structured questionnaires among 400 eligible participants whom were identified through systematic household sampling from eight districts in Aden, Yemen. Eligible participants were Yemeni community members who were ≥18 years, living more than 10 years in Yemen. The questionnaire included questions surrounding the participants’ COVID-19 knowledge, attitudes, and prevention practices during the pandemic. Total KAP scores were calculated. Univariate and bivariate statistical analyses were made. RESULTS: From January to May 2021 we conducted 400 questionnaires with Yemeni community members. The average age was 41.5±14.5 years (range 18-86 years). The results show that the participants had an intermediate knowledge (53%) and fair attitude (58%) scores. However, participants reported very poor COVID-19 prevention practices with having a score of (11%). Only 25%, (100/400) practiced social distancing, 25% (98/400) wore a mask, and only 6% (27/400) of participants accepted (at least one dose of) the COVID-19 vaccine. Factors associated with adequate knowledge were being male, married, and surprisingly those having a primary and middle school education levels (p < 0.05). Also participants whom were diagnosed with having COVID-19 or had a family member diagnosed with COVID-19 (vs. those not diagnosed OR=2.08, 95% CI 1.07-3.78, p<0.05) were more likely to know that the vaccine protects against COVID-19 severe infection and were more likely to take apply good practice as taking the vaccine (OR=2.65, 95% CI 1.17-6.00, p<0.05) compared to those who were not. CONCLUSION: The findings raises the need of community-oriented education programs for COVID-19 which incorporates consideration of associated factors to improve the level of public knowledge, attitudes, and practices.